ANALISIS PENGARUH CLIENT IMPORTANCE, AUDIT TENURE DAN AUDIT DELAY TERHADAP KUALITAS AUDIT - Fathin Ramadha Tuffahaty (2023)
This research is a quantitative research derived from secondary data in the form of annual reports on the IDX website or each entity. This study aims to identify, analyze and test the effect of client importance, audit tenure and audit delay on audit quality during the 2017-2021 observation year. This study uses various industrial sector entities listed on the Indonesia Stock Exchange in 2017-2021 as a population and applies a purposive sampling method in sample screening. So that obtained a sample of 200 samples consisting of 40 entities. The analysis technique used in testing the hypothesis uses a logistic regression analysis model with a significance level of 5% (0.05) with SPSS 26 software as a research test tool. The results of this study indicate that (1) client importance has a significant negative effect on audit quality, (2) audit tenure has a significant positive effect on audit quality and (3) audit delay has no significant effect on audit quality.